2008
DOI: 10.1108/00070700810900594
|View full text |Cite
|
Sign up to set email alerts
|

The gateway to a Canadian market‐driven agricultural economy

Abstract: Purpose -The purpose of this paper is to provide a structured demand chain design framework that can be linked with gateway and corridor management practices. Design/methodology/approach -The model in this paper presents supply and demand thrusts that could leverage Canada's position in international food trade. Findings -Since a direct correlation exists between the wealth of a nation and how it consumes food, the paper first presents five utilities and several factors that are perceived differently by custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to this research, industry consolidation and the vertical integration of the supply chains is the area of the future research. Charlebois (2008) provided a structured demand chain design frame work that can be linked with gate way and corridor management practices. In this research a model for supply and demand thrust was used to leverage food trade and suggested a demand chain design framework.…”
Section: Perishable-nonperishablementioning
confidence: 99%
See 1 more Smart Citation
“…According to this research, industry consolidation and the vertical integration of the supply chains is the area of the future research. Charlebois (2008) provided a structured demand chain design frame work that can be linked with gate way and corridor management practices. In this research a model for supply and demand thrust was used to leverage food trade and suggested a demand chain design framework.…”
Section: Perishable-nonperishablementioning
confidence: 99%
“…The responsibilities for food perish ability, wastage, poor supply chain practices lies equally with all the stakeholders of the chain. Charlebois (2008) suggested the framework for demand chain design as shown in Figure 7. This framework emphasizes competencies such as processes, assets and tasks as well as coordination mechanism and selection of the required chain members needed in upstream phases of the chain to satisfy particular group of customers.…”
Section: Vertical Integrationmentioning
confidence: 99%